Linearly Tunable CMOS Voltage Differencing Transconductance Amplifier (VDTA) - Worapong Tangsrirat (My University, 2019)
This paper proposes an alternative way to implement the CMOS voltage differencing transconductance amplifier (VDTA) with linearly tunable. It has been designed by using the floating current source (FCS) and the current squaring circuit. The circuit achieves its linear tunability by squaring the long-tail biasing current of the FCS. In this way, the transconductance gains of the proposed CMOS VDTA can be varied linearly through adjusting the DC bias currents. As an application example, the proposed VDTA is used in the design of an actively tunable voltage-mode multifunction filter. The derived filter possesses the following desirable properties: simultaneous realization of three standard filter functions; employment of only two grounded capacitors; and electronic tunability of w o and Q . The performance of the proposed circuit and its filter design application were examined by PSPICE simulations with TSMC 0.25- m m CMOS real process technology.
Keywords: Transconductance; Operational transconductance amplifier; Biasing; Analog and Mixed-Signal Circuit Design